Assessment of Changes in Behavior and Quality of Life after Monobloc Treatment in Children with Obstructive Sleep Apnea or Primary Snoring - Eser Çapan; Hülya Kılıçoğlu; Hande Uzunçıbuk (Galenos Yayinevi, 2024)
Objective: The aim of this study was to examine the quality of life and behavioral disorders in children with obstructive sleep apnea (OSA) or primary snoring, as well as how these problems changed after monobloc treatment. Methods: Fourteen children with primary snoring and 16 children with OSA who had skeletal class II malocclusion due to mandibular retrognathia were treated with monobloc appliances. To investigate the relationship between behavioral disorders and quality of life, parents were asked to complete four questionnaires: attention deficit and hyperactivity disorder (ADHD) scale, strength and difficulties questionnaire (SDQ), pediatric sleep questionnaire (PSQ), and Pittsburgh sleep quality scale (PSQS). Mann-Whitney U and Wilcoxon signed-rank tests were used to evaluate the data. Results: According to the results of the PSQ and PSQS, an increase in sleep quality was observed after monobloc treatment. The decrease in the total ADHD score at the end of the treatment was found to be statistically significant in both the OSA (p<0.01) and snoring (p<0.01) groups. According to the SDQ scores, the increase in the social behavior score and the decrease in the peer bullying score in the snoring group were statistically significant (p<0.05). Conclusion: The use of a monobloc appliance in pediatric patients exhibiting primary snoring and OSA resulted in a notable reduction in sleep-breathing disorder symptoms and a notable enhancement in their overall quality of life. Based on the analyses of the questionnaires, it was concluded that the increase in sleep quality improved the pediatric patients' quality of life after orthodontic treatment with orthodontic monobloc appliances.